THEORETICAL PRINCIPLES FOR IMPLEMENTING PUBLIC-PRIVATE PARTNERSHIP IN THE LOGISTIC SUPPORT SYSTEM OF THE UNITS' ACTIVITIES OF THE NATIONAL GUARD OF UKRAINE - Kovalchuk, Yurii; Bielai, Serhii (Honor and Law, 2025)
Theoretical principles for introducing public-private partnerships into the logistics support system for the National Guard of Ukraine formations are studied. It is demonstrated that the problems of introducing mechanisms of public-private partnership in the field of defence capability of the state are of current relevance. It is determined that the use of private organizations to perform assigned tasks allows qualified commercial structures to supply units, thus guaranteeing the most effective and efficient use of resources. The involvement of private partners in NATO operations is also an important factor in increasing the combat capabilities of NATO troops, its member states, and partner countries. It is proven that public-private partnership includes a limited range of combat functions and a wide range of logistics support functions. The need to develop risk-management strategies that fully anticipate the consequences of incorporating public-private partnership elements is justified. Furthermore, the need to compose potential military-response options for situations in which any further use of private partners becomes irrational is substantiated. Prospects for further scholar research are indicated, which will be aimed at developing mechanisms for public-private partnership in peacetime, in case of emergencies, and under conditions of hostilities.